Employing Tryptone as a General Phase Transfer Agent to Produce Renal Clearable Nanodots for Bioimaging. Issue 30 (27th April 2015) - Liu, Fuyao; He, Xiuxia; Zhang, Junping; Zhang, Huimao; Wang, Zhenxin
<x xml:space="preserve">Abstract</x> Hydrophobic ultrasmall nanoparticles synthesized in nonpolar solvents exhibit great potential in biomedical applications. However, a major challenge when applying these nanomaterials in biomedical research is the lack of a versatile strategy to render them water dispersible while preserving the hydrodynamic diameter (HD) to be less than 8 nm for efficient renal clearance. To address this problem, tryptone is employed as the novel ligand to fabricate a simple, versatile, and inexpensive strategy for transferring hydrophobic NaGdF4 nanodots (3 nm in diameter) from organic phase into aqueous phase without any complicated organic synthesis. The paramagnetic properties of NaGdF4 nanodots are well retained after the phase transfer process. In particular, the tryptone–NaGdF4 nanodots have ultrasmall HD (ca., 7.5 nm), which greatly improves their tumor accumulation and facilitates renal clearance within 24 h postinjection. The as‐prepared tryptone–NaGdF4 nanodots can also be further functionalized with other molecules for extensively biomedical and bioanalytical applications. Furthermore, the proposed strategy can easily be extended to transfer other types of inorganic nanoparticles from hydrophobic to hydrophilic for facilitating biomedical applications.